Cry1Ba1-mediated toxicity of transgenic Bergera koenigii and Citrus sinensis to the Asian citrus psyllid Diaphorina citri - Orbović, Vladimir; Ravanfar, Seyed Ali; Achor, Diann S.; Shilts, Turksen; Ibanez-Carrasco, Freddy; Banerjee, Rahul; El-Mohtar, Choaa; Stelinski, Lukasz L.; Bonning, Bryony C. (Frontiers in Insect Science, 2023)
The Asian citrus psyllid, Diaphorina citri, vectors the bacterial causative agent of citrus greening disease, which has severely impacted citrus production on a global scale. As the current repeated application of chemical insecticides is unsustainable for management of this insect and subsequent protection of groves, we investigated the potential use of the bacteria-derived pesticidal protein, Cry1Ba1, when delivered via transgenic citrus plants. Having demonstrated transformation of the Indian curry leaf tree, Bergera koenigii, for Cry1Ba1 expression for use as a trap plant (Ravanfar et al., 2022), we produced transgenic plants of Duncan grapefruit, Citrus paridisi, Valencia sweet orange, Citrus sinensis, and Carrizo citrange, C. sinensis x Poncirus trifoliata, for expression of Cry1Ba1. The presence of the cry1ba1 gene, and cry1ba1 transcription were confirmed. Western blot detection of Cry1Ba1 was confirmed in most cases. When compared to those from wild-type plants, leaf discs from transgenic Duncan and Valencia expressing Cry1Ba1 exhibited a “delayed senescence” phenotype, similar to observations made for transgenic B. koenigii. In bioassays, significant reductions in the survival of adult psyllids were noted on transgenic B. koenigii and Valencia sweet orange plants expressing Cry1Ba1, but not on transgenic Duncan grapefruit or Carrizo citrange. In contrast to psyllids fed on wild type plants, the gut epithelium of psyllids fed on transgenic plants was damaged, consistent with the mode of action of Cry1Ba1. These results indicate that the transgenic expression of a bacterial pesticidal protein in B. koenigii and Valencia sweet orange offers a viable option for management of D. citri, that may contribute to solutions that counter citrus greening disease.